Un Código civil perfecto y bien calculado. El proyecto de 1821 en la historia de la codificación - Petit Calvo, Carlos Manuel (Historia del Derecho, 2020)
A study of the (incomplete) draft of the Civil Code drawn up by the Cortes in 1821, within the framework of the ideas and texts of the contemporary European codification. It reconstructs the parliamentary life of the text in the Spanish Cortes and the biographies of the deputies who worked on it, in particular Nicolás Mª Garelly. The analysis of three relevant issues addressed by Garelly and his colleagues - namely the theory of legislation, the conditions affecting the legal status of individuals, their civil rights - completes the monograph, which also includes a new edition of the printed booklet (December 1821) that constitutes our sole source of knowledge.